Temporal artery biopsy: is there any value in examining biopsies at multiple levels? - Chakrabarty, A (2000)
Aims—To analyse the cost-effectiveness of three strategies for examining temporal artery biopsies based on data from cases examined over the past 10 years. Methods—Of a total of 172 temporal artery biopsies, five were unsuitable for further analysis, 47 had already had levels cut, and 120 had levels cut as part of the study. All the biopsies were examined blind before and after levels. A tree with eventual diagnostic outcomes for different strategies was constructed and economic and sensitivity analyses performed. Welcan units were used to assess technical workload. Results—Only one of the 132 initially normal cases and two of 14 diagnosed with periarterial lymphocytic infiltration (PALI) revealed giant cell arteritis after examining the tissue at multiple levels. Fifteen cases (8.9%) showed PALI not previously observed. The marginal cost for each extra case of giant cell arteritis detected was 83.5 Welcan units for a strategy of routine levels on all sections, and 21 Welcan units for a strategy of only cutting levels if PALI was present on the initial section. These costs were sensitive to the frequency of giant cell arteritis in cases with PALI and to the relative extra cost of moving from cutting single section to routine levels. Conclusions—Routinely examining a temporal artery biopsy at multiple levels does not increase the diagnostic yield of the test, although selective further examination may be indicated in some cases. The significance of PALI is uncertain. The cost-benefit of the different strategies in terms of clinical decision making revolve around the perceived risk inherent in not making a diagnosis of giant cell arteritis. Key Words: temporal artery biopsy • economic analysis • decision analysis